Slope Stability Analysis of Landslide in the Nepalese Himalaya: A Case Study of Kuiyadaha Landslide, Gokuleshor, Baitadi - Baral , Sanjay; Tiwari , Ram Chandra (Himalayan Journal of Applied Science and Engineering, 2025)
Landslides are a common geologic feature in the Nepalese topography. Primary concern of this paper was the numerical modelling along with the case study. This paper describes an investigation into the slope stability of the Kuiyadaha Landslide. The objective of the research is to find out the factor of safety by performing numerical modelling in fully saturation and fully dry condition without vegetation and earthquake loading of creeping landslide of Baitadi District. A back analysis technique was employed to estimate soil strength parameters, where the friction angle (f) was varied, assuming zero cohesion, to achieve a Strength Reduction Factor (SRF) of unity. The derived soil parameters were then utilized to compute the factor of safety (FOS) and recommend stabilization measures, including reducing the groundwater table (GWT) and applying toe loading. Slope stability study was performed using a variety of computational tools, including Cubit, Cygwin, ParaView, Easymesh, AutoCAD, SW DTM, and Tecplot. The SPECFEM3D_GEOTECH software, which uses the Spectral Element Method (SEM), played a crucial role in the analysis. This study discovered that the Kuiyadaha Landslide is extremely prone to slope failure during the rainy season. The stability analysis facilitated the design of effective mitigation measures, highlighting the importance of reduced GWT and toe loading for slope stabilization. Validation of the findings was performed using the Phase2 commercial software. A strong correlation of 0.965 between the results from Phase2 and SPECFEM3D_GEOTECH confirms the reliability of the analysis. This research demonstrates the utility of back analysis and advanced numerical modeling in evaluating and mitigating landslide risks.